Clinical medicine for Intensive Care especialists. Questions to an expert. - Alfredo Darío Espinosa Brito; Juan Francisco Rocha Hernández (Medisur)
Conception, organization, and development of Intensive Care Medicine is one of the greatest contribution that medical care services brought to the professional practice of doctors and paramedic personnel in the second part of the 20th centrury. In our country, since the 70’s years, this field was incorporated in our National Health System to the daily work of our professionals as to the patients expectations, in an almost an imperceptible way. Twenty polemical questions were asked to an expert, about several current dilemmas in this field. The questions and the answes are only a motivation for new debates in medical services, in medical education activities and in research.